Keefektifan Manajemen Sekolah Bertaraf Internasional di SMA Negeri Kota Yogyakarta - Afid Burhanuddin (LPPM Press, 2010)
this study aims to investigate the effectiveness of the management of International Standard State Senior High Schools in Yogyakarta City in termsof the Context, Input, Process, and Product components. This study was an evaluation research study employing the CIPP (Context, Input, Process, Product)evaluation model. This study employed the quantitative descriptive approach. The research subjects comprised 2 principals, 27 teachers, and 250 students ofSMA Negeri 1 dan 3 Yogyakarta. The students were selected by means of the purposive sampling technique. The data were collected through observations,documents, interviews, and questionnaires. The data were analyzed using the SPSS Program Version 16.0. The results of the study are as follows. 1) Theeffectiveness in terms of the Context component is in the moderate category (73.51%), 2) The effectiveness in terms of the Input component is in the highcategory (76.33%), 3) The effectiveness in terms of the Process components is in the moderate category (74.68%), 4) The effectiveness in terms of the Productcomponent is in the high category (88.13%).